(untitled) (Economic and Political Thought, 2019)
Having adopted Henry Kissinger’s thesis that after 1989/1991 the world entered a transition period from the two-polar world via the present one-polar world /the US hegemony to the multi-polar world that followed, one must agree with the thesis that the transition period must be characterised by farreaching dynamic of changes. Analysing Poland’s attempts to find place in the world of the transition period, the author carried out an analysis of internal and external conditions of Polish foreign policy in the period, and next included it in the analysis of selected Polish regional initiatives of the transition period. The author concentrates on four main initiatives of that type, i.e. the Visegrad cooperation, “the Bucharest format”, the Three Seas Initiative and the new Polish initiative concerning the Central-European part of the Chinese project of the New Silk Road known as the ‘16+1’ initiative.